2017
DOI: 10.1016/j.bmcl.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis and biological evaluation of ω-hydroxy polyunsaturated fatty acids

Abstract: ω-Hydroxy polyunsaturated fatty acids (PUFAs), natural metabolites from arachidonic acid (ARA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) were prepared via convergent synthesis approach using two key steps: Cu-mediated C-C bond formation to construct methylene skipped poly-ynes and a partial alkyne hydrogenation where the presence of excess 2-methyl-2-butene as an additive that is proven to be critical for the success of partial reduction of the poly-ynes to the corresponding cis-alkenes witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 43 publications
5
23
0
Order By: Relevance
“…This agrees with literature suggesting that n-3 PUFA are better ligands for GPR120 than n-6 PUFA [22]. Moreover, these data are consistent with recent results that metabolites of n-3 PUFA are much more potent agonists for the TRPV1 receptor than metabolites of ARA [55]. N-3 PUFA seemingly exhibit distinctive mechanisms on brown vs. beige precursor cells, although GPR120 is involved in both brown and beige fat development.…”
Section: Proposed Mechanism Established From Animal Studiessupporting
confidence: 92%
“…This agrees with literature suggesting that n-3 PUFA are better ligands for GPR120 than n-6 PUFA [22]. Moreover, these data are consistent with recent results that metabolites of n-3 PUFA are much more potent agonists for the TRPV1 receptor than metabolites of ARA [55]. N-3 PUFA seemingly exhibit distinctive mechanisms on brown vs. beige precursor cells, although GPR120 is involved in both brown and beige fat development.…”
Section: Proposed Mechanism Established From Animal Studiessupporting
confidence: 92%
“…Hwang et al (2000) compared the activation of TRPV1 of several endogenous arachidonic acid metabolites and found that the strongest endogenous activator was 12-HpETE, which is formed by 12-LOX. Our own research compared 12-HpETE with 20-HETE and identified it as an even more potent TRPV1 agonist (Bubb et al, 2013;Kroetz & Xu, 2005;Wen et al, 2012) and others have confirmed our observations that 20-HETE acts as a TRPV1 agonist (Hwang et al, 2017;Wang et al, 2020;Zhang et al, 2018). However, whether 20-HETE via activation of TRPV1 is a pivotal ligand for the channel in the setting of inflammation is unknown.…”
supporting
confidence: 78%
“…In this way, linoleic acid (LA 18:2) serves as a precursor to several other molecules such as arachidonic acid (AA 20:4) [47]. Then, this is followed by hydroxylation or epoxidation reactions catalyzed by cytochrome P450 (CYP450) enzymes, resulting in the generation of hydroxyeicosatetraenoic acids (HETEs), such as 20-hydroxyeicosatetraenoic acid (20-HETE), or epoxieicosatrienoic acids (EETs) [49,50] (Figure 2).…”
Section: Products Derived From Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…α-linolenic acid (ALA 18:3) produces eicosapentaenoic acid (EPA 20:5) and docosahexaenoic acid (DHA 22:6) [47], which are precursors of 20-hydroxyeicosapentaenoic acid (20-HEPE) and 22-hydroxyeicosapentaenoic acid (22-HDoHE) [50] (Figure 3). α-linolenic acid (ALA 18:3) produces eicosapentaenoic acid (EPA 20:5) and docosahexaenoic acid (DHA 22:6) [47], which are precursors of 20-hydroxyeicosapentaenoic acid (20-HEPE) and 22hydroxyeicosapentaenoic acid (22-HDoHE) [50] (Figure 3).…”
Section: Products Derived From Polyunsaturated Fatty Acidsmentioning
confidence: 99%